Pengaruh Celebrity Endorsement, Brand Image, dan Kepercayaan Konsumen terhadap Keputusan Pembelian Produk Brand Fashion Elora Girl Wear - Ni Made Sintya; Luh Putu Mahyuni (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Purchasing decisions are the stages buyers go through in making choices about products from the fashion brand Elora Girl Wear. Several factors influence purchasing decisions, including celebrity endorsement, brand image, and consumer trust. The purpose of this study was to determine the influence of celebrity endorsement, brand image, and consumer trust on purchasing decisions, both partially and simultaneously. The research sample for the fashion brand Elora Girl Wear used accidental sampling, with 100 respondents. Data collection was conducted through questionnaires. The data analysis techniques used in this study were Multiple Linear Regression, Analysis of Determination, Simultaneous Significance Test (F Test), and Partial Significance Test (t Test). The results showed that: (1) Celebrity endorsement has a positive effect on purchasing decisions. Brand image has a positive effect on purchasing decisions. (3) Consumer trust has a positive effect on purchasing decisions. (4) Celebrity endorsement, brand image, and consumer trust simultaneously have a positive effect on purchasing decisions.